STRENGTHENING THE MSME FINANCING ECOSYSTEM THROUGH SUSTAINABLE FUNDING ACCESS STRATEGIES IN SOUTH KONAWE REGENCY - Akbar Wahbi; Munawir Makmur; Agus Zul Bay (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze strategies for strengthening the financing ecosystem of Micro, Small, and Medium Enterprises (MSMEs) through sustainable financing access in Konawe Selatan Regency. The primary issue addressed is the limited accessibility of formal financing faced by rural entrepreneurs amid the demands of Indonesia's national green economic transition. This research employed a qualitative approach using a case study method. Data were collected through semi-structured interviews with 20 key informants, including MSME actors, regulators, and banking representatives, supported by participatory field observations and policy document analysis. The findings reveal four major themes: business legality constraints as the primary structural barrier, low financial literacy related to Environmental, Social, and Governance (ESG) principles, the strategic role of Village-Owned Enterprises (BUMDes) as local financial intermediary institutions, and challenges in adapting financial technology in areas with limited infrastructure. These findings contribute to the development of a community-based financial ecosystem model. The study concludes that strengthening the financing ecosystem requires policy synergy to facilitate MSME formalization and the development of inclusive green microfinance products. Practical implications include the need to enhance the managerial capacity of BUMDes and simplify licensing bureaucracy at the regional level. Future studies are recommended to quantitatively examine the effectiveness of this partnership model across broader regional contexts.